2011
DOI: 10.1103/physrevlett.107.188101
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystems with Mutually Exclusive Interactions Self-Organize to a State of High Diversity

Abstract: Ecological systems comprise an astonishing diversity of species that cooperate or compete with each other forming complex mutual dependencies. The minimum requirements to maintain a large species diversity on long time scales are in general unknown. Using lichen communities as an example, we propose a model for the evolution of mutually excluding organisms that compete for space. We suggest that chain-like or cyclic invasions involving three or more species open for creation of spatially separated sub-populati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 39 publications
3
83
0
Order By: Relevance
“…In experiments with Escherichia coli, for example, it has been shown that arranging the bacteria on a Petri dish is crucial for keeping all three competing strains alive [8,36]. Accordingly, simulations of spatial rock-paper-scissors and related games of cyclic dominance have a long and fruitful history [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is firmly rooted in methods of statistical physics. In general, if the mobility in the population is sufficiently small [7], the spatial rock-paper-scissors game leads to the stable coexistence of all three competing strategies, whereby the coexistence is maintained by the spontaneous formation of complex spatial patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments with Escherichia coli, for example, it has been shown that arranging the bacteria on a Petri dish is crucial for keeping all three competing strains alive [8,36]. Accordingly, simulations of spatial rock-paper-scissors and related games of cyclic dominance have a long and fruitful history [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is firmly rooted in methods of statistical physics. In general, if the mobility in the population is sufficiently small [7], the spatial rock-paper-scissors game leads to the stable coexistence of all three competing strategies, whereby the coexistence is maintained by the spontaneous formation of complex spatial patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The critical value was found to be approximately γ c ≈ 0.055, for L = 192 [28,35]. For larger systems L ∈ 256, 320 we find larger critical values γ c ≈ 0.1.…”
Section: Fraction Of Time In High-and Low-statementioning
confidence: 64%
“…The mean diversity shows a sharp transition from high-to low-values at γ ≈ 0.055 when α is close to zero and N = 192 2 [28,35] as shown in Figure 1(a). However, the fluctuation of the diversity turned out to be significant for larger α (see Fig.…”
Section: A Diversity and Frozen Boundary Lengthmentioning
confidence: 94%
See 1 more Smart Citation
“…Investigating three strands of E. coli bacteria with cyclic interactions, it has been shown that biodiversity can not be preserved unless spacial structure is imposed by arranging the bacteria on a petri dish [7,8,26]. These results have been reproduced in Monte Carlo simulations [6,[27][28][29], but even though many different analytical approaches have been applied, exactly how spatial structure stabilizes the system is still an open problem [30][31][32][33].…”
mentioning
confidence: 99%